EneRGY EFFICIENT SKI LODGE Design: The case of Erzurum - Balo, Figen; Sua, Lutfu S.; Boydak, Hazal (Nova Science Publishers, Inc., 2023)
The building design process is currently experiencing some significant adjustments. Buildings that are more environmentally friendly are being promoted all around the world as a way to combat climate change. Furthermore, the concept of Building Information Modelling (BIM) is replacing stand-alone design methodologies. Many benefits have been documented as a result of BIM adoption, ranging from time savings to energy and cost savings. Upon finalization of the plan with all of its material specifications and components, the accuracy of the performed analysis is critical for sustainability in energy efficient planning. There are variety of methods and analytic tools that may be used to anticipate important metrics and values such as energy use, U value, and energy conservation. Building information modeling can be used in the early stages of planning to analyze the metrics and values of planning before diving into the more sensitive matters of construction's design. In this study, a ski lodge was designed in Erzurum, where one of Turkey's largest ski resorts is located. The building envelope of the ski lodge is planned as a sandwich wall. Different construction (bims, brick, and gas concrete) and insulation materials (phenolic foam, polyurethane, and polyisocyanure) were used in the building envelope. Basalt stone, andesite stone, and slate stone, which were extracted from Erzurum province and used as wall covering material in the building sector, were applied to all design alternatives. Considering the optimum insulation thickness in the building envelope for the region, the appropriate thickness values of the insulation materials were used in the analysis. A tile roof was considered for the roof of the building, taking into account the heavy snowfall in the region. BIM-based Green Building Studio simulation was used to identify the most energy efficient building envelope among all alternatives. In the light of the provided evaluations, it is aimed to be a study that will guide the public of the region, decision makers, engineers, and contractors working in the construction sector on energy efficient buildings. Similarly, this study is also important for being an exemplary study in terms of creating more energy efficient structures in different regions by considering the materials suitable for the regional conditions and the features of the designed building. © 2023 Nova Science Publishers, Inc. All rights reserved.
Keywords: BIM; Building envelope; Energy efficiency; Green buildings studio; Insulation materials; Natural stone